Physical, morphological and biochemical effects of prenatal ultrasound exposure on rabbit fetus / Farah Wahida Ahmad Zaiki - Ahmad Zaiki, Farah Wahida (Institute of Graduate Studies, UiTM, 2016)
Ultrasound is extensively used in various clinical specialties throughout the developed world since it was perceived to lack in bioeffects. Somehow, through the advances in the capability of ultrasound equipment that triggered greater image processing power, the revision of potential bioeffects is needed to be corroborated. Hence, this study is designed to determine the physical, morphological and biochemical effects on fetus development. This in-vivo experimental study involved twelve pregnant rabbits, exposed to ultrasound exposure durations of 30, 60 and 90 minutes in the middle of the stipulated gestational stages (1st stage; gestational day (GD) 6-7, 2nd stage; GD 17-18, 3rd stage; GD 28-29). Acoustic output parameters were kept constant (frequency = 7.09 MHz, intensity (ISPTA) = 49.4 W/cm2, power = 56.0 W, thermal index (TI) = 0.2 and mechanical index (MI) = 1.0). The rabbits were euthanized and data were analyzed using SPSS 21. Total 136 fetuses (1st stage, n = 34 (25%); 2nd stage, n = 28 (21%); 3rd stage, n = 74 (54%)) were analyzed for physical, structural and ultrastructural morphological, biochemical and haematological analyses. Physical analysis found to have significant differences in fetal weight between exposed and control groups at all stages (P < 0.001, P = 0.01, P < 0.001, respectively) with a negative correlation between different exposure durations and fetal weight at 1st and 3rd stages (P = 0.02, r = -0.40, P = 0. 04, r = -0.23, respectively)…